PENGARUH KEPEMILIKAN INSTITUSIONAL, KONSERVATISME AKUNTANSI DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Nurlaeli, Dedeh; Angraini, Dila (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to determine the influence of institutional ownership, accounting conservatism, and sales growth on partial and simultaneous (together) tax avoidance in food and beverage sub-sector companies listed on the Indonesian Stock Exchange (BEI) for the 2018–2022 period. The type of research used is quantitative research and uses data sources in the form of annual reports on food and beverage sub-sector companies listed on the Indonesian Stock Exchange (BEI) for the 2018–2022 period. The data collection technique uses documentation and literature study methods, and data analysis is calculated using the Eviews Version 12 software program. The results of this research are that institutional ownership partially has no effect on tax avoidance, accounting conservatism partially has an effect on tax avoidance, and partial sales growth has no effect on tax avoidance, jointly (simultaneously) institutional ownership, accounting conservatism, and sales growth influence tax avoidance.